Isu-Isu Kontemporer dalam Dunia Kerja - Khoirul Annisa; Fatmatu Haerunnisa; Machdum Bachtiar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The world of work is changing rapidly due to globalization, digitalization, and technological innovation. This paper discusses contemporary issues in the workplace, including outsourcing, artificial intelligence and automation, flexible and hybrid work arrangements, layoffs, and compensation systems. The study applies a qualitative method using a literature review approach by examining books, journals, laws, and official reports relevant to the topic. The results show that outsourcing is often adopted to increase efficiency and organizational focus, but it also raises concerns about job security and the protection of workers’ rights. Artificial intelligence and automation improve productivity and operational speed, yet they may replace routine jobs and create a need for upskilling and reskilling. Flexible and hybrid work models provide greater work-life balance and adapt well to modern organizational needs, although they may also cause communication problems, burnout, and blurred boundaries between work and personal life. Layoffs remain a serious issue because they affect workers’ economic conditions and psychological well-being, so fair and transparent policies are needed. Compensation systems also play an important role in motivating employees, improving loyalty, and supporting organizational sustainability. Overall, this study concludes that the modern workplace requires adaptive regulations, continuous human resource development, and a balanced strategy between innovation and worker protection to build a fair, productive, and sustainable employment environment.